Analysis of Landslide Vulnerability Levels and Disaster Mitigation Based on Geographic Information Systems GIS in Prambanan District, Sleman Regency - Sigit, Agus Anggoro; Fikriyah, Vidya; Dewi, Hapsari Kusuma; Ibrahim, Mohd Hairy (International Journal for Disaster and Development Interface, 2025)
Prambanan District is one of the sub-districts in Sleman Regency that is prone to landslide threats, one of which is due to the topography in Prambanan District which has a steep slope of 18.53%. According to a statement from the Disaster Risk Reduction Forum (FPRB) in Prambanan District, there are 5 villages that are prone to landslides and based on the latest data from the Regional Disaster Management Agency (BPBD) in 2021 there were 16 incidents. This study utilizes the application of Geographic Information Systems for vulnerability analysis using 5 parameters: slope, soil type, geological type, rainfall and land use. This study aims to 1) analyze the distribution of landslide susceptibility levels in Prambanan District, Sleman Regency, 2) analyze the dominant factors that cause landslide vulnerability in Prambanan District, Sleman Regency, 3) analyze what mitigation efforts can be done to minimize losses due to disasters. Landslide in Prambanan District, Sleman Regency. The method used in this research is the survey method using the unit of analysis of land units. The sampling method in this study used stratified random sampling based on the strata, land units that were adjusted to the level of landslide susceptibility. The data analysis methods used are tiered overlay analysis, frequency table analysis, landslide hazard map analysis and field surveys. The results of this study indicate that the level of vulnerability to landslides in Prambanan District is dominated by moderate vulnerability. Moderate vulnerability covers 17 land units, is a S5-IL-STH, S5-III-L-STH, S5-VLT, S5-II-LT, S5-II-L-STH, S5-IV-LP, S5-IV-LK , S5-IV-L-STH, V8-I-RCK-SI, F1-I-RCK-SI, F1-I-GK-SI, F1-II-RCK-SI, F1-II-L-SI, F1 -ILT, F1-IL-SI, S2-II-LT, S2-III-LT. The dominant factors causing landslide susceptibility in Prambanan District are bulk and soil type. Disaster mitigation efforts in Prambanan District based on the results of analysis and field surveys are divided into 2 forms, structural mitigation and non-structural mitigation.